Variants in HCFC1 and MN1 genes causing intellectual disability in two Pakistani families - Syeda Iqra Hussain; Nazif Muhammad; Shahbaz Ali Shah; Adil u Rehman; Sher Alam Khan; Shamim Saleha; Yar Muhammad Khan; Noor Muhammad; Saadullah Khan; Naveed Wasif (BMC, 2024)
Abstract Background Intellectual disability (ID) is a neurodevelopmental condition affecting around 2% of children and young adults worldwide, characterized by deficits in intellectual functioning and adaptive behavior. Genetic factors contribute to the development of ID phenotypes, including mutations and structural changes in chromosomes. Pathogenic variants in the HCFC1 gene cause X-linked mental retardation syndrome, also known as Siderius type X-linked mental retardation. The MN1 gene is necessary for palate development, and mutations in this gene result in a genetic condition called CEBALID syndrome. Methods Exome sequencing was used to identify the disease-causing variants in two affected families, A and B, from various regions of Pakistan. Affected individuals in these two families presented ID, developmental delay, and behavioral abnormalities. The validation and co-segregation analysis of the filtered variant was carried out using Sanger sequencing. Results In an X-linked family A, a novel hemizygous missense variant (c.5705G > A; p.Ser1902Asn) in the HCFC1 gene (NM_005334.3) was identified, while in family B exome sequencing revealed a heterozygous nonsense variant (c.3680 G > A; p. Trp1227Ter) in exon-1 of the MN1 gene (NM_032581.4). Sanger sequencing confirmed the segregation of these variants with ID in each family. Conclusions The investigation of two Pakistani families revealed pathogenic genetic variants in the HCFC1 and MN1 genes, which cause ID and expand the mutational spectrum of these genes.